PEMODELAN HIDROLOGI BERBASIS SPASIAL UNTUK IDENTIFIKASI DAN ANALISIS DAERAH RAWAN BANJIR DI DAS LAMASI - Nursaputra, Munajat; Syahrul R, A. Muhammad; Rijal, Syamsu; Fa'iq, Muhammad (Universitas Muhammadiyah Gorontalo, 2024)
This study investigates the changes in flood inundation areas in the Lamasi Watershed, focusing on the integration of HEC-RAS and SWAT models from 2013-2022 with projections up to 2031. This research is motivated by the increased frequency and extent of flooding in DAS Lamasi, attributed to land use changes and hydrological variability. The methodology employed involves hydrological simulation using the SWAT model to estimate river discharge based on historical land use, climate, and topography data. The output from the SWAT model is then integrated into the HEC-RAS model to simulate flood distribution and extent. The Flow Regime Coefficient (KRS) is also analyzed to assess flow quality and identify flood risk indicators. The results indicate an expected increase in flood inundation area from 1,825.88 hectares in 2021 to 1,860.62 hectares in 2031. The KRS analysis reveals that 17 sub-basins in poor condition in the downstream areas exhibit a high risk of flooding. Based on these findings, the study recommends the development of mitigation strategies including enhanced drainage infrastructure and more effective land management. This study provides crucial insights for the planning of flood management and risk mitigation in DAS Lamasi, supporting efforts to adapt to the impacts of land use changes and climate dynamics in the future.